Silver Nanoparticles for Biosensing and Drug Delivery: A Mechanical Study on DNA Interaction - Katarína Nemčeková; Patrícia Dudoňová; Tomáš Holka; Sabína Balážová; Michaela Hornychová; Viktória Szebellaiová; Monika Naumowicz; Pavol Gemeiner; Tomáš Mackuľak; Miroslav Gál; Veronika Svitková (Biosensors)
Silver nanoparticles (AgNPs) have attracted tremendous attention in recent years due to their unique physicochemical properties, including pronounced surface plasmon resonance, tunable size, and amenability to functionalization. These attributes underpin the growing interest in AgNPs as SMART nanocarriers for targeted drug delivery and as active components in biosensing platforms. In this work, we discuss various synthesis strategies for AgNPs—ranging from conventional chemical methods to green approaches—and highlight their subsequent functionalization with anticancer drugs, notably doxorubicin (DOX). We also examine the potential of AgNPs in biosensor applications, emphasizing electrochemical and optical detection modalities capable of monitoring drug release, oxidative stress, and relevant biomarkers. Our experimental data support the conclusion that AgNPs can effectively improve therapeutic efficacy by exploiting tumor-specific conditions (e.g., lower pH) while also enhancing biosensor sensitivity via surface plasmon resonance and electrochemical signal amplification. We provide a thorough discussion of the results, including mechanistic aspects of reactive oxygen species (ROS) generation, drug release kinetics, and sensor performance metrics. Overall, AgNP-based nanocarriers emerge as a powerful platform to address current challenges in precision oncology and medical diagnostics.